High precision underwater 3D imaging of non-cooperative target with frequency comb. (April 2022) - Zhao, Haihan; Xu, Xinyang; Qian, Zhiwen; Shi, Haonan; Sun, Wanzhong; Zhai, Jingsheng; Wu, Hanzhong
Highlights: Utilizing dispersive interference to accomplish 3D imaging of underwater target. Complete high-precision imaging of underwater non-cooperative target. The imaging accuracy of the target is ensured by two different algorithms. The error of target imaging is less than 8 µm at a range of 2.5 m underwater. Abstract: High-precision underwater imaging technology has an important role in underwater navigation and identification, underwater pipeline inspection, sinker docking, and underwater vibration measurement. Due to the different mechanisms of underwater measurement sources, such as 3D gated imaging and streak tube imaging, the accuracy of underwater target imaging can reach the millimeter level. In this paper, we propose a high-precision underwater imaging method based on frequency combs. When measuring the non-cooperative target underwater, the spectrogram is modulated due to the strong dispersion property of water. After that, for the gained spectrogram, we use two algorithms, i.e., center offset frequency and phase slope, to obtain the distance and imaging, respectively. By comparing with reference values, the underwater experimental results combining two algorithms show an agreement within 8 μm in the range of 2.5 m, corresponding to 3.2 × 10 −6 relative precision. This work can provide a strong guarantee and support for high-precision underwater applications.